A comparative study between anterior and posterior approach for bipolar hemiarthroplasty in intracapsular fracture neck of femur - Juneja, Johney; Asiger, Mohzin; Sharma, Ishan; Andrews, Nitin; Joshi, Vinay; Sen, Ramesh (International Journal of Research in Orthopaedics, 2021)
Background: The present study was undertaken to to compare the efficacy of treatment of intracapsular neck of femur fracture operated by anterior and posterior approaches. Methods: A total 100 patients of either sex, aged >65 years with intracapsular neck femur fracture were operated with hemiarthroplasty. The patients were divided into two equal groups and patients were operated alternatively one with anterior approach and the second with posterior approach. Functional outcomes were compared using Harris hip score and range of movements assessed clinically. Hip function and final outcome measures were noted and compared between two groups. Results: The mean age of patients was 63.1±5.3 years in group A and 65.8±5.4 years in group B with female to male ratio was 1.7:1 for group A and 1.8:1 for group B. Operating time for group A and for group B was 65 and 78 minutes respectively. Mean intraoperative blood loss was 120 ml in group A and 150 ml in group B. The most common complication in both the groups were infection and rate in group A was 9.70% and in group B was 13.50%. Posterior approach carried an increased risk of prosthetic dislocation as compared to anterior approach. There was no intraoperative mortality seen in follow up period. Conclusions: Anterior approach for hip hemiarthroplasty in elderly population with intracapsular femoral neck fractures provided significant benefit in early postoperative period when compared to the posterior approach in terms of duration of surgery, intraoperative blood loss, time of recovery, hip dislocation rate.